Wireless measurement and dynamic contact analysis on the root stress of a light-load spur gear drive. Issue 3 (2nd September 2017) - Zhou, Changjiang; Hu, Bo; Chen, Siyu; Ma, Lin
Abstract: This paper carries out the experimental and numerical investigations on the root stress of a light-load spur gear drive. An improved gear test rig is developed to enable the dynamic root stress of a light-load spur gear drive to be wirelessly measured, and the signals of root strain, rotational speeds and torques of input/output gear shafts are sent or received wirelessly. After the random electrical noise is eliminated by multi-point average method, the key parameters of dynamic contact analysis on the root stress (rotational speeds and torque) are obtained, and the root strain signal is converted into root stress. Based on the curve of the measured root stress, the impact of meshing teeth and the alternative variation in the single and double pair gear meshing can be attained quantitatively. The geometric model of gear is developed by the generative machining principle and the coordinate transformation method. Then, the dynamic contact analysis is performed by the display centre difference method to obtain the maximum tensile stress of the tooth root, which is compared with the results in literature as well as the wireless measurement data. It shows that the wireless measurement approach and the developed method of dynamic contact analysis are effective and efficient.